2018
DOI: 10.1111/jzo.12585
|View full text |Cite
|
Sign up to set email alerts
|

Covariates streamline age‐specific early life survival estimates of two chelonian species

Abstract: Delayed maturity and high survival rates of immatures and adults characterize long‐lived species’ life histories. Understanding how these traits interact in stochastic environments is essential to understand early life in long‐lived species and to assist conservation planning. Unfortunately, available information of demographic traits in immatures are often fragmentary and the logistical difficulties of capturing and recapturing this cohort leave little room for improvement. Published immature chelonian surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 51 publications
4
18
0
Order By: Relevance
“…for turtles during drought periods; Roe & Georges, 2008b), our results did not indicate a decrease in survival during the dry period despite the differences found in movement rates between periods. Juveniles had consistently lower estimated survival rates than adults, which is consistent with the literature (Arsovski et al 2018;Hamer et al, 2018;Iverson, 2018). However, their survival increased far more drastically with pond connectivity, as measured by Eigenvector centrality, and was especially low in poorly connected ponds.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…for turtles during drought periods; Roe & Georges, 2008b), our results did not indicate a decrease in survival during the dry period despite the differences found in movement rates between periods. Juveniles had consistently lower estimated survival rates than adults, which is consistent with the literature (Arsovski et al 2018;Hamer et al, 2018;Iverson, 2018). However, their survival increased far more drastically with pond connectivity, as measured by Eigenvector centrality, and was especially low in poorly connected ponds.…”
Section: Discussionsupporting
confidence: 89%
“…However, because freshwater turtles are long-lived and most studies report only annual survival, we also estimated annual survival using the delta method approximation for estimating sampling variances and deriving 95% confidence intervals (Powell 2007;Saumure, Herman, & Titman, 2007), thereby providing comparable estimates with those reported elsewhere (e.g. Arsovski et al 2018;Canessa et al, 2016;Congdon, Gotte, & McDiarmid, 2016). In addition, for complementary purposes, we provide in Appendix S2 the annual estimates of apparent survival derived from single-state CJS modelling applied to our data pooled into one record per year.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…However, we did not find any treatment difference in turtles' propensity to emerge, perhaps because there was no potential cost associated with not emerging. Additionally, hiding in cover is likely innate for this species, as this is probably the most efficient antipredator behavior for juveniles which are smaller and have less rigid shells than adults [3,18,26]. As with our predator recognition assay, future experiments might show greater treatment differences if shelter emergence tests incorporate aspects of our other assays, such as determining if turtles will differ in emergence propensity based on whether food or predator cues are present.…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile turtles (order Testudines) often have lower estimated survival rates than adults, with predation assumed to be the primary cause of mortality [16,17]. Older, larger animals are less vulnerable to predation, in part due to a larger and thicker shell that can be a successful deterrent for many predators [3,18]. Additionally, wild turtles often do not reach reproductive sizes for upwards of 1-2 decades, so increasing juvenile growth rates should allow individuals to be closer to reproductive size upon release [19].…”
Section: Introductionmentioning
confidence: 99%
“…The wide range in immature apparent survival estimates among sites is likely due in part to site-specific factors such as habitat quality or predator abundance (Smith et al 2013) but may also be influenced by the size distribution of animals comprising the immature class. Predicted annual survival increases with increasing size in immature desert tortoises (from 54% at 60 mm MCL to 95% at 150 mm MCL; McGovern 2019) and age in other turtle species (Fernández-Chacón et al 2011, Arsovski et al 2018; however, few studies have investigated whether survival also increases over the immature period in gopher tortoises. Wright (2016) and McKee (2019) reported that annual apparent survival of subadult gopher tortoises is significantly higher than that of juveniles, although neither provided separate estimates for the hatchling stage.…”
Section: Discussionmentioning
confidence: 99%